Integrating Bojonegoro Local Wisdom into BIPA Level A1 Listening Section - Nazzah Yusva Jayyidah; Chyntia Heru Woro Prastiwi; Moh. Fuadul Matin (IKIP PGRI Bojonegoro, 2026)
Listening plays an essential role in beginner-level language learning because it provides learners with the primary source of linguistic input. However, listening materials in Bahasa Indonesia bagi Penutur Asing (BIPA) instruction often receive less attention than other language skills and frequently provide limited exposure to local cultural contexts. This study aims to investigate the integration of Bojonegoro local wisdom into listening materials for A1 BIPA learners. The study employed a Research and Development approach using the Four-D (4D) model consisting of the Define, Design, Develop, and Disseminate stages. The developed materials were integrated into a bilingual digital flipbook containing listening activities based on various aspects of Bojonegoro local wisdom, including Kayangan Api, Wayang Thengul, Tari Thengul, the Samin community, Batik Jonegoroan, traditional foods, and local beverages. The findings reveal that the listening materials employ simple vocabulary, short sentence structures, and familiar communicative situations appropriate for beginner learners. Furthermore, local wisdom functions as a meaningful cultural context that supports listening comprehension while introducing learners to regional cultural identities. The use of a digital flipbook also provides opportunities for repeated listening practice and autonomous learning. This study suggests that integrating local wisdom into listening materials can support both language acquisition and cultural understanding in beginner-level BIPA instruction.